The cholesteryl-ester transfer protein isoform (CETPI) and derived peptides: new targets in the study of Gram-negative sepsis - Eréndira G. Pérez-Hernández; Víctor De la Puente-Díaz de León; Ismael Luna-Reyes; Blanca Delgado-Coello; José Sifuentes-Osornio; Jaime Mas-Oliva (BMC, 2022)
Abstract Background Sepsis is a syndrome where the dysregulated host response to infection threatens the life of the patient. The isoform of the cholesteryl-ester transfer protein (CETPI) is synthesized in the small intestine, and it is present in human plasma. CETPI and peptides derived from its C-terminal sequence present the ability to bind and deactivate bacterial lipopolysaccharides (LPS). The present study establishes the relationship between the plasma levels of CETPI and disease severity of sepsis due to Gram-negative bacteria. Methods Plasma samples from healthy subjects and patients with positive blood culture for Gram-negative bacteria were collected at the Intensive Care Unit (ICU) of INCMNSZ (Mexico City). 47 healthy subjects, 50 patients with infection, and 55 patients with sepsis and septic shock, were enrolled in this study. CETPI plasma levels were measured by an enzyme-linked immunosorbent assay and its expression confirmed by Western Blot analysis. Plasma cytokines (IL-1β, TNFα, IL-6, IL-8, IL-12p70, IFNγ, and IL-10) were measured in both, healthy subjects, and patients, and directly correlated with their CETPI plasma levels and severity of clinical parameters. Sequential Organ Failure Assessment (SOFA) scores were evaluated at ICU admission and within 24 h of admission. Plasma LPS and CETPI levels were also measured and studied in patients  with liver dysfunction. Results The level of CETPI in plasma was found to be higher in patients with positive blood culture for Gram-negative bacteria that in control subjects, showing a direct correlation with their SOFA values. Accordingly, septic shock patients showing a high CETPI plasma concentration, presented a negative correlation with cytokines IL-8, IL-1β, and IL-10. Also, in patients  with liver dysfunction, since higher CETPI levels correlated with a high plasma LPS concentration, LPS neutralization carried out by CETPI might be considered a physiological response that will have to be studied in detail. Conclusions Elevated levels of plasma CETPI were associated with disease severity and organ failure in patients  with Gram-negative bacteraemia, defining CETPI as a protein implicated in the systemic response to LPS.